The Role of Creative Cluster Savamala on Belgrade Repositioning in Global Hierarchies - Simeunčević Radulović, Sanja V; Stupar, Aleksandra (Arhitektura i urbanizam, 2016)
Urban competitiveness in post-industrial society largely depends on the strength of city’s creative economy. It is represented by its position in global urban hierarchies, as an indicator of its importance and attractiveness for people and companies. Creative clusters present a way to stimulate creative economy in the city because the spatial concentration of creative companies and people additionally stimulates exchange of ideas and knowledge. Article explores complex dynamic between creative economy, cities and global hierarchies. The focus is on the role of creative clusters in the process of global positioning, especially in the case of Belgrade. The city has significantly improved its position in the global urban hierarchy – from a non-existing node in 2000, to the “beta” level of global cities in 2008 (according to GaWC global urban hierarchy). Furthermore, in just four years (2008-2012), Belgrade improved its rank for three positions. This period overlaps with several interesting events - e.g. the initial phase of the largest regional creative festival and the development of a creative cluster in Savamala. Consequently, the article will emphasize the importance of this district in the global repositioning of Belgrade.